Pengaruh Susu Sapi dan Protein Whey Terhadap Kekerasan Email Gigi Setelah Demineralisasi - Liesma Dzulfia; Mia Damiyanti; Ellyza Herda (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
Caries has high prevalence oral problem in Indonesia. Bovine milk and its product has been proven to have anticariogenic effect. To analyze effect of immersed enamel surface in bovine milk and protein whey after demineralization. Twenty one specimens of human premolar tooth enamel measured its hardness before the treatment, after demineralized with 1% citric acid (pH 2.5), and after immersed in bovine milk, whey protein and aquades for 90 minutes. Enamel hardness number was measured using Knoop Microhardness Tester with 25 g load for 5 seconds. Statistical analysis with Repeated Anova showed significant increased of enamel hardness in bovine milk and protein whey groups (p<0.05). There was no significant differences between group immersed in bovine milk and whey protein (p>0.05). Bovine milk and whey protein could remineralize enamel surface but not be able to restore the original value of email surface hardness.